Refleksi Pemilu 2024 terhadap Politisasi Agama di Media Sosial Perspektif Teori Double Movement Fazlur Rahman - Abdul Hamid; Anwar Sanusi; Achmad Lutfi; Muhamad Sofi Mubarok; Debi Fajrin Habibi5 (Gunung Djati Conference Series, 2023)
This study aims to discuss the reflection of the 2024 election on the politicization of religion on social media from the perspective of Fazlur Rahman's double movement theory. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion of this study indicate that it is necessary to carry out socio-historical contextualization of religion through Fazlur Rahman's double movement theory, which is known for its dual movements, the socio-historical affirmation must be studied as there is still humiliation of a group which ultimately results in divisions between groups. Of course this has to go back to the socio-historical beginning of the verses of the Qur'an which upheld justice. The verses of the Qur'an instruct humans not to generate hate speech against other people. Talking about the politicization of religion, this must be avoided by the public so that they are not easily provoked by politics in the name of religion. Theoretically and practically, this research is expected to have benefits and usefulness implications as an initial study of reflections on the 2024 Election on the politicization of religion on social media from the perspective of Fazlur Rahman's double movement theory. This study recommends government agencies, religious leaders, and the public not to be easily provoked by politics in the name of religion.